Quantum Entropy-Based Encryption for Securing Communication Devices in TNI AU Space Units - Lisdi Inu Kencana; H.A Danang Rimbawa; Bisyron Wahyudi (Penerbit Jurnal Indonesia, 2024)
The rising threat of cyber-attacks demands advanced encryption technologies to ensure secure communication. This study evaluates the performance and security of the Quantum Shieldz Cipher integrated with Quantum Entropy-Based Encryption (QEBE) to address the limitations of conventional encryption methods. The main objective is to test the system's ability to generate unpredictable encryption keys, detect interception attempts, and resist quantum-based cyber threats. Experiments were conducted under various operational scenarios, including standard conditions, high interference, and high bandwidth environments, with a focus on its implementation for strategic communication in the Indonesian Air Force (TNI AU).The results show that QEBE effectively generates highly secure encryption keys using the Quantum Random Number Generator (QRNG), significantly reducing the risk of brute-force attacks. The system successfully detects interception by identifying changes in qubit states during data transmission. The implementation within TNI AU demonstrates its effectiveness in securing critical communication systems that require robust protection. However, the system relies heavily on stable network infrastructure with high bandwidth to maintain optimal performance. Compared to conventional methods, QEBE provides superior security and resistance to quantum-based attacks, albeit with a slight trade-off in processing speed. In conclusion, the Quantum Shieldz Cipher integrated with QEBE shows significant potential for enhancing secure communication systems, particularly in critical operations within TNI AU. This technology is a promising solution to safeguard against evolving cyber threats and quantum-based attacks.